Isolation And Screening Of Marine Bacteria Producing Antibiotics Against Human Pathogens - PREM ANAND.T; C. CHELLARAM; C. FELICIA SHANTHINI (International Journal of Pharma and Bio Sciences, 2011)
The need for the development of new antibiotics to counter drug resistance in bacterial pathogens has been stressed by various researchers worldwide. As the discovery of novel chemical classes have been in decline for the past two decades, the need to exploit new resources in search for effective chemicals with novel mechanism of actions is imperative. Marine bacteria are such a resource yet to be tapped, and the potential it offers is vast. The principal objective of this present investigation was to isolate and screen marine bacteria for the production of bioactive metabolites. Associated bacterial strains were isolated from 10 species of sponges, 12 species of algae, 4 species of crabs, 3 species of ascidians, sediment, one species each of sea cucumber, sea urchin and jellyfish. Gut microflora was isolated from 3 species of mollusc, biofilm bacteria from dead corals and dead oyster shell and egg bacterial symbionts from crab eggs and eggs of molluscs. A total of 633 strains were isolated during a period of two years. In the antibiotic production test 170 strains were found to be active against the five human pathogens (E.coli, Staphylococcus aureus, Pseudomonas aeruginosa, Bacillis substilis and Candida albicans).In the genus level identification of the potential strains, Alteromonas sp. was found to be the dominant antibiotic producer.